Sri Lanka's Climate Smart Governance Dashboard: training manual - Alahacoon, Niranga; Amarnath, Giriraj; Sivananthan, Piriyanka (International Water Management Institute, 2024)
Sri Lanka’s geographical and climatic conditions expose it to significant natural disaster risks, including floods, droughts, landslides, and cyclones. These recurring hazards disrupt socio-economic stability, causing loss of life, displacement, and environmental degradation. To combat these challenges, Sri Lanka emphasizes sustainable development and disaster preparedness. The Climate-Smart Governance (CSG) Dashboard enhances Sri Lanka’s capacity to address climate challenges effectively by streamlining data, fostering collaboration, and supporting evidence-based strategies. Its user-friendly interface, robust functionalities, and global adaptability make it vital to building climate resilience and advancing national and international sustainable development.